Residual stress measurement in composite materials - Asundi, Anand Krishna (2008)
To evaluate the residual stresses experimentally, an optical measurement technique in conjunction with the hole-drilling method was developed. The holde-drilling method has been successfully used to determine the residual stresses in metals.